DISPENSATIONS MARRIAGE THROUGH THE APOSTOLIC DATARIA. FUNCTIONS AND PROBLEMS IN THE XVIII AND XIX CENTURIES. - Henarejos López, Juan Francisco (Revista de Historia Social y de las Mentalidades, 2017)
This paper focuses on the study of the Roman Apostolic Dataria and its influence on the processing and granting of marriage dispensations in Spain. Although various contributions made by the international historiography, there are still many unresolved issues. The diverse matrimonial law and its evolution will be marked by the performance of this Roman institution at various times, especially in the eighteenth and nineteenth centuries. Our goal is to provide response to an institution of great importance in obtaining and validation of marriage dispensations. A the same time, investigate the conflict generated in this institution during the Old Regime. For it have been used different documents from the Vatican Secret Archives and Archives and Spanish libraries